Psychosomatic medicine and the policy of humanization of SUS: discomfort in the contemporary world - Rossatti Duval, Melissa; de Lima Oliveira, Silene (O Mundo da Saúde, 2010)
This article presents a reflection and a theoretical revision about the policy of humanization proposed by the Brazilian National Policy of Humanization (PNH-HumanizaSUS) and brings the contribution of psychosomatic medicine, by means of its theoretical concepts, for the discussion and therapeutic action in the relationship between professionals and users of the health system. The article also briefly approaches the structure and the present moment of the system of health, delineating a brief historical critic for discussing the concept of humanization and its interrelations with human subject and their communities in health services, in which there is a complementing between managing and taking care. The importance of a model of management that allows for an expansion of the present social networks in the health system – a system in which transformations may happen in the way one takes care, with a proactive attitude of human subject – is questioned, contributing for an effectiveness in the process health-disease in the contemporary world.